OPTIMALISASI FUNGSI PENYIDIKAN OLEH BADAN NARKOTIKA NASIONAL - Nadhira Nadhira (Jurnal Kriminologi Indonesia, 2010)
This research is a study about investigative function given to NNB (National Narcotics Board) since 12th October 2009. Based on 75th article of Laws Number 35 Year 2009 on Narcotics, the NNB has the rights to investigate, something that used to be done only by investigators of Police Department. This research is about description of the process of investigation by NNB’s detective since the law is implemented, and their relationship with other investigator from Police Department. This Research uses descriptive qualitative approach, where the data collection is done by using literature study, Interview, and observation to NNB. This research concludes that the NNB’s investigators has done their functions according to 75th article of the law, even though there are still some obstacles need to repaired to improve the performance of NNB’s investigators.